SOFTWARE FOR SIMULATION OF TECHNOLOGICAL ADAPTATION OF THE OPTICAL INSTRUMENTS SYSTEMS - N. K. Artioukhina; V. A. Marchyk (Приборы и методы измерений)
Programs for calculation and analysis of optical systems of any class are provides. The most effective was to combine the programs into a complex with the general system of mathematical models. A characteristic feature is to unify the exchange of information between these programs and software systems Opal and Zemax.